1991
DOI: 10.1002/j.1460-2075.1991.tb07854.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes are positioned with base pair precision adjacent to the alpha 2 operator in Saccharomyces cerevisiae.

Abstract: Analysis of the chromatin structure of minichromosomes containing the binding site for the yeast alpha 2 repressor protein by indirect end‐labeling has previously indicated that nucleosomes are stably positioned over sequences adjacent to the alpha 2 operator in the presence of the repressor. Development of a primer extension assay for nucleosome position now allows a more detailed examination of the location of these nucleosomes relative to the operator sequence, and indicates that nucleosomes are precisely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
213
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(231 citation statements)
references
References 45 publications
17
213
0
1
Order By: Relevance
“…Previous studies revealed that the α2/Mcm1 repressor, in conjunction with the Ssn6-Tup1 corepressor and the Isw2 complexes establishes an array of positioned nucleosomes to form a repressive chromatin structure [15,17,20,21,[28][29][30]32]. Our results imply that the positioned nucleosomes in the repressive chromatin function to limit the accessibility of at least a certain class of activators in vivo, therefore supporting the idea that nucleosome positioning plays a vital role in repression by α2/Mcm1.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies revealed that the α2/Mcm1 repressor, in conjunction with the Ssn6-Tup1 corepressor and the Isw2 complexes establishes an array of positioned nucleosomes to form a repressive chromatin structure [15,17,20,21,[28][29][30]32]. Our results imply that the positioned nucleosomes in the repressive chromatin function to limit the accessibility of at least a certain class of activators in vivo, therefore supporting the idea that nucleosome positioning plays a vital role in repression by α2/Mcm1.…”
Section: Discussionsupporting
confidence: 86%
“…The α2 operator is located in the region of 1535-1565 nucleotides (nt) in TALS. Nucleosome IV is positioned both translationally and rotationally adjacent to the α2 operator in the region of 1376-1522 nt in TALS in α cells, but not in a cells, as shown previously [17,23]. These minichromosomes have been utilized to examine the binding of Gal4 [7][8][9][10][11] (Fig.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…A translational signal for nucleosome positioning generated by specific protein binding is also observed on studying a2-mediated repression of a-cell-type specific gene expression in haploid a Levinger 119851 Ambrose et al [1990] cells and in diploid a / a cells in yeast [reviewed by Herskowitz, 19891. The a2-repressor, in association with another promoter-specific protein MCM1, represses gene expression apparently by placing nucleosomes next to the a,-MCM1 complex, resulting in nucleosome occupancy of the TATA box of the adjacent genes [Shimizu et al, 1991;Roth et al, 19921. Five similar cases have been studied; in three of these, nucleosomes have been carefully mapped.…”
Section: Sv40 Minichromosomementioning
confidence: 99%